2017
DOI: 10.2109/jcersj2.17026
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and mechanical properties of glass and glass-ceramic electrolytes in the system Li<sub>3</sub>BO<sub>3</sub>&ndash;Li<sub>2</sub>SO<sub>4</sub>

Abstract: Low-melting oxide glasses are promising as electrolytes for all-solid-state lithium rechargeable batteries. Glasses in the pseudobinary system Li 3 BO 3 Li 2 SO 4 were prepared by a mechanochemical technique. Raman spectra revealed that the glasses contained no macroanions which form networks but consisted only of Li + ions and two discrete ortho-oxoanions, BO 3 3¹ and SO 4 2¹. The density and molar volume increased and elastic moduli decreased with an increase in the Li 2 SO 4 content in the glasses. The heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…[11][12][13]38] The ionic conductivity obtained in this study almost matches with these reported values; therefore, the higher ionic conductivity was probably attributed to the amorphous NMC-Li 2 SO 4 matrix. Owing to the decrease in grain boundary area, the electronic conductivity increased even when the insulating Li 2 SO 4 component was added.…”
Section: Electrical Conduction Properties Of the Amorphous Materialssupporting
confidence: 84%
See 2 more Smart Citations
“…[11][12][13]38] The ionic conductivity obtained in this study almost matches with these reported values; therefore, the higher ionic conductivity was probably attributed to the amorphous NMC-Li 2 SO 4 matrix. Owing to the decrease in grain boundary area, the electronic conductivity increased even when the insulating Li 2 SO 4 component was added.…”
Section: Electrical Conduction Properties Of the Amorphous Materialssupporting
confidence: 84%
“…[18] In addition, there are advantages in the use of amorphous materials to achieve higher capacities and better cycle characteristics owing to the open and random structures. [12,13] All-solid-state cells using this amorphous active material operated as secondary batteries at 100 °C. [22][23][24] The obtained amorphous LiCoO 2 -Li 2 SO 4 positive electrode material exhibited the best charge-discharge performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thin film was deposited at 200°C on a Si substrate and a 90Li 3 BO 3 ·10-Li 2 SO 4 (mol%) electrolyte pellet. 15,16 The substrate temperature was chosen for improving characteristics of electrode-electrolyte interfaces based on a previous report. 17 To avoid exposure of the deposited film to the atmosphere, a PLD vacuum chamber connected to an Ar-filled grove box was used.…”
Section: Preparation Of the Thin Film Electrodementioning
confidence: 99%
“…So far, there are numerous studies based on glass and glass-ceramic-based materials as electrolytes for batteries, with limited studies as electrodes where the present work falls into action. 7,8 2 | METHODS…”
Section: Introductionmentioning
confidence: 99%